Inter-Religious Prejudice in A Multicultural Society - Sustanto Sustanto; Kholid Mawardi (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Prejudice between religious believers in a multicultural society is a negative view or stereotype that is formed against a particular religion or individual based on their religion. The writing of this scientific article is to use literature research, researchers examine theories, concepts, definitions, understandings of the variables studied to find their connection. The result of writing this article is Prejudice in the religious context is a behavior that will threaten the integrity of the Indonesian nation as a multicultural nation. This prejudiced behavior is formed in a person due to individual, sociological and cultural psychological factors. Religious prejudice will trigger discrimination and violence in society. If this behavior continues, it does not rule out the spirit of multiculturalism that is expected to evaporate by itself. Prevention of prejudice in religion can be done by increasing the value of the prejudiced group, opening communication, conditioning the environment to internalizing social norms.